Pengaruh Perputaran Kas, Perputaran Piutang Dan Perputaran Persediaan Terhadap Profitabilitas: Studi Kasus pada Perusahaan Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Periode 2017-2019 - Setiawan, Hendra; Putri, Mellanysha Andria; Muanas, Muanas; Alamsyah, Richad (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
Cash turnover is a ratio used to measure the number of times cash enters the company in a given period. Receivables Turnover is a ratio used to measure how quickly the return of payments and receivables is collected in a period. Inventory turnover is an efficiency ratio that shows how effective a company's inventory is, it measures the number of times a company sells its total inventory on average throughout the year. This study aims to find out whether Cash Turnover, Receivables Turnover and Inventory Turnover have a partial or simultaneous effect on Profitability in Food and Beverage companies listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. In this study, sampling was done by saturated sampling. The population in the study was a food and beverage sub-sector company listed on the Indonesia Stock Exchange. From 28 companies obtained 24 companies that were used as research sample data. There were 57 total sample data from 72 sample data after the outlier test. This study used SPSS 27 with statistical methods used is multiple linear regression. The results showed that; (1) Cash Turnover negatively and significantly affects Profitability, (2) Receivable Turnover has no effect and is insignificant to Profitability, (3) Inventory Turnover has no effect and is insignificant to Profitability. Simultaneously Cash Turnover, Receivable Turnover and Inventory Turnover have significant impact on Profitability. The R Square value of 0.249 indicates that a 24.9% change in the company's Profitability can be explained by the free variables associated with this study, while the remaining 75.1% is explained by other factors not included in the research regression model. Keywords: Cash Turnover, Receivables Turnover, Inventory Turnover and Profitability.